Remap-TPS with Xmind: A Learning Model to Improve Students’ Digital Literacy and Learning Outcomes - Kurniaty, Irna; Zubaidah, Siti; Prabaningtyas, Sitoresmi (Bioedusiana: Jurnal Pendidikan Biologi, 2023)
Digital literacy is critical in the current era of digitalization. However, several studies show that digital literacy in Indonesia still needs to be improved and strengthened. Less than optimal digital literacy can impact low student learning outcomes. Therefore, this research aims to analyze the effect of the Reading Concept Mapping Think Pair Share (Remap -TPS) learning model assisted by the Xmind application to improve digital literacy and student learning outcomes. This research was conducted at SMA Negeri 9 Malang, Lowokwaru, East Java, Indonesia, in the odd semester of the 2023/2024 academic year. This research is a quasi-experiment with a pretest-posttest non-equivalent design. Respondents in this study were classes X Science 3 and X Science 4 with 70 students. Data was collected through questionnaires to measure digital literacy and essay questions to measure learning outcomes. The research results show that the Remap-TPS learning model significantly affects digital literacy and student learning outcomes. This indicates that the Remap-TPS model, assisted by the Xmind application, can be an alternative solution in designing learning processes to empower digital literacy and student learning outcomes.